Internal flexibility and collective bargaining in the European Union during the Great Recession: An analysis at the establishment level - Santos Ruesga Benito; María Isabel Heredero de Pablos; Julimar Da Silva Bichara; Laura Pérez Ortiz; Ana Vi\~nas Apaolaza (Kiel Institute for the World Economy (IfW), 2019)
The paper's main objective is to analyze the collective bargaining response in terms of internal flexibility during the Great Recession (GR) in five EU countries (Spain, Germany, France, Italy, United Kingdom), and three economic sectors (industry, commerce and hospitality, and financial services and real estate), at the establishment level (ECS2013 database). The theoretical frame-work used is linked to the varieties of unionism. Using a descriptive statistical analysis and a probit model, this paper presents new evidences. However, the responses were heterogeneous between countries and sectors, the use of internal functional flexibility has been more intense than the numerical and salary internal flexibility. Moreover, it is related to the intensity of GR. These results, in general, while requiring a more detailed analysis of the effects of the GR on internal flexibility in the EU countries, contribute to introducing a new perspective in the socioeconomic literature about the collective bargaining and internal flexibility.
Keywords: J51; 330; China; collective bargaining; internal flexibility; Great Recession; establishment level